LA-ICP-MS U-Pb zircon dating of rocks of the Jacareacanga Group, Tapajós Domain, Amazon Craton, Brazil - Jenny Alexandra Ortega Cardozo; Marcelo Vasquez; Marco Antonio Galarza Toro (Brazilian Journal of Geology)
Abstract The Jacareacanga Group comprises mafic to ultramafic schists, metacherts, quartzites, pelitic paragneisses, and amphibolites related to siliciclastic-chemical sedimentation and mafic-ultramafic volcanism. These rocks of the Jacareacanga Group correspond to turbidite-related sediments and oceanic crust basalts of a back-arc or trench basin of the early magmatic Cuiú-Cuiú Arc of the Tapajós Domain in the Amazon Craton. Field data and petrographic analysis support the new zircon U-Pb ages obtained through LA-ICP-MS for the rocks of the Jacareacanga Group. A ± 10% concordance criterion applied, along with an exclusion of ages < 2000 Ma to mitigate interference from later events, such as granitic intrusions. Two pelitic paragneisses yielded 207Pb/206Pb ages between 2008 and 2042 Ma and mica schist ages of ca. 2056 Ma, considered to be the maximum sedimentation age of the protoliths of metasedimentary rocks. Zircon populations from the Rhyacian to the Mesoarchean indicate provenance from adjacent cratonic areas. This study shows that the Jacareacanga Basin was formed during the early Orosirian. The oldest detrital zircon ages support provenance from a magmatic arc basin of a continental margin comprising Rhyacian to Mesoarchean crust.